Escherichia coli Bloodstream Infections in Patients at a University Hospital: Virulence Factors and Clinical Characteristics - Daga, Ana Paula; Koga, Vanessa Lumi; Soncini, João Gabriel Material; de Matos, Caroline Martins; Perugini, Marcia Regina Eches; Pelisson, Marsileni; Kobayashi, Renata Katsuko T.; Vespero, Eliana Carolina (Frontiers in Cellular and Infection Microbiology, 2019)
Extraintestinal pathogenic Escherichia coli (ExPEC) isolates are responsible for many bloodstream infections. The aim of this study was to characterize E. coli isolated from the bloodstreams of patients (n= 48) at the University Hospital in Brazil. Epidemiological data were obtained through the analysis of medical records and laboratory tests. By PCR analysis, we investigated the presence of virulence factors (VFs), pathogenicity islands (PAIs), extended-spectrum β-lactamase (ESBL), phylogenetic classifications (A, B1, B2, C, D, E, and F) and molecular genotype by enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR). The mortality analysis showed that 33.3% of the deaths were associated with bacteraemia due to E. coli infections; in addition, an age between 60-75 years (p<0.001; OR=6.3[2.1-18.9]) and bacteraemia with an abdominal origin (p=0.02; OR=5 [1.2-20.5]) were risk factors for the severity of the infection. Additionally, the presence of the afa gene was associated with mortality due to E. coli bacteraemia (p=0.027; OR=11.4 [1.5-85.7]). Immunosuppression (27.1%), intestinal diseases (25.0%) and diabetes (18.8%), were prevalent among patients, and most of the bacteraemia cases were secondary to urinary tract infections (50.0%). The serum resistance gene traT was present in 77.1% of isolates, group capsular 2 (kpsMT II) was present in 45.8% and the K5 capsule was present in 20.8% of isolates. The isolates also showed a high prevalence for the siderophore yersiniabactina (fyuA) (70.8%) and PAI IV536 (77.1%). Phylogenetic analysis showed that group B2 (45.8%) was the most prevalent, and was the phylogroup that had a higher prevalence of VFs and PAIs. However, in this study, a considerable number of isolated bacteria were classified as group B1 (18.8%) and as group E (14.6%). Eight (16.7%) isolates were resistant to third and fourth generation cephalosporin and group CTX-M-1 (CTX-M-15) was the most prevalent ESBL type. The molecular genotyping showed two clonal lineages and several isolates that were not related to each other. This study provides additional information on the epidemiological and molecular characteristics of E. coli bloodstream infections in Brazil.